PELATIHAN PENETASAN TELUR PADA MAHASISWA MAGANG MBKM PRODI PETERNAKAN UNIVERSITAS MUHAMMADIYAH SIDENRENG RAPPANG - Angga Nugraha; Helmi Rafia Rahmi; Nirwana Mulyadi; Novian Surya Dharma; Rafi Adriyan Fadhilah; Faradita Aprilia Dafri; Mohammad Irfan (Penerbit Widina, Widina Media Utama, 2026)
This egg hatching training activity aimed to improve the knowledge and technical skills of Merdeka Belajar Kampus Merdeka (MBKM) internship students from the Animal Science Study Program in understanding the integrated egg hatching process, from egg receiving to producing day old chicks (DOC). The activity was conducted at PT. Satwa Indo Perkasa using a direct practice (hands-on training) method under the supervision of field lecturers and company supervisors. The training stages included egg receiving, egg grading, pre-warming, egg setting in setter machines, operation of setter and hatchery machines, egg turning, egg transfer, and pull chick processes. The results showed that students gained practical experience and technical understanding related to hatchery management, temperature and humidity control, and proper handling of hatching eggs according to poultry industry standards. Furthermore, the training enhanced students’ competencies in hatchery management, supporting their work readiness and technical expertise in the poultry farming sector. ABSTRAKKegiatan pelatihan penetasan telur ini bertujuan untuk meningkatkan pengetahuan dan keterampilan mahasiswa magang Program Merdeka Belajar Kampus Merdeka (MBKM) Program Studi Peternakan dalam memahami proses penetasan telur secara terintegrasi, mulai dari penerimaan telur hingga menghasilkan day old chick (DOC). Kegiatan dilaksanakan di PT. Satwa Indo Perkasa dengan menggunakan metode praktik langsung (hands-on training) di bawah bimbingan dosen pembimbing lapangan dan supervisor perusahaan. Tahapan kegiatan meliputi penerimaan telur, grading telur tetas, pre warming, pengaturan telur pada mesin setter, pengoperasian mesin setter dan hatchery, turning, transfer telur, hingga proses pull chick. Hasil kegiatan menunjukkan bahwa mahasiswa memperoleh pengalaman praktis dan pemahaman teknis mengenai manajemen penetasan telur, pengendalian suhu dan kelembapan, serta penanganan telur tetas yang sesuai standar industri perunggasan. Pelatihan ini juga mampu meningkatkan kompetensi mahasiswa dalam bidang hatchery sehingga dapat mendukung kesiapan kerja dan penguasaan keterampilan teknis di sektor peternakan unggas.